Hierarchical Metal–Polymer Hybrids for Enhanced CO2 Electroreduction. Issue 19 (1st April 2021) - Jia, Shuaiqiang; Zhu, Qinggong; Chu, Mengen; Han, Shitao; Feng, Ruting; Zhai, Jianxin; Xia, Wei; He, Mingyuan; Wu, Haihong; Han, Buxing
Abstract: The design of catalysts with high activity, selectivity, and stability is key to the electroreduction of CO2 . Herein, we report the synthesis of 3D hierarchical metal/polymer–carbon paper (M/polymer‐CP) electrodes by in situ electrosynthesis. The 3D polymer layer on CP (polymer‐CP) was first prepared by in situ electropolymerization, then a 3D metal layer was decorated on the polymer‐CP to produce the M/polymer‐CP electrode. Electrodes with different metals (e.g. Cu, Pd, Zn, Sn) and various polymers could be prepared by this method. The electrodes could efficiently reduce CO2 to desired products, such as C2 H4, CO, and HCOOH, depending on the metal used. For example, C2 H4 could be formed with a Faradaic efficiency of 59.4 % and a current density of 30.2 mA cm −2 by using a very stable Cu/PANI‐CP electrode in an H‐type cell. Control experiments and theoretical calculations showed that the 3D hierarchical structure of the metals and in situ formation of the electrodes are critical for the excellent performance. Abstract : A series of metal–polymer hybrids constructed from various metals and different polymers showed outstanding performance for the electroreduction of CO2 with simultaneously enhanced activity, selectivity, and stability. The 3D hierarchical structure of the metals and in situ formation of the electrodes were found to be critical for high performance.